Comparative with recent trends, design, and functionalities of various operating systems - Abu-Jassar Amer; Jamal Khalaf Omar (Multidisciplinary Journal of Science and Technology, 2024)
The article compares and contrasts three widely used operating systems: Macintosh, Linux, and Windows. The fundamentals of storage and data management, architecture, protection, adaptability, and other subjects are the main areas of attention when examining them. In this study, these subjects are contrasted. An overview of the key subjects and the numerous parallels and discrepancies in the fundamental usage of operating systems are provided by this research study. This research focuses on the fundamental advantages and disadvantages of each operating system. Each type of operating system has a unique set of variations in its architecture and makeup.
Keywords: Operating Systems; Artificial Intelligence